Cannabis and its derivatives for the use of motor symptoms in Parkinson's disease: a systematic review and meta-analysis. (May 2021) - Thanabalasingam, Susan J.; Ranjith, Brandan; Jackson, Robyn; Wijeratne, Don Thiwanka
Background: Recent changes to the legal status of cannabis across various countries have renewed interest in exploring its use in Parkinson's disease (PD). The use of cannabinoids for alleviation of motor symptoms has been extensively explored in pre-clinical studies. Objective: We aim to systematically review and meta-analyze literature on the use of medical cannabis or its derivatives (MC) in PD patients to determine its effect on motor function and its safety profile. Methods: We reviewed and analyzed original, full-text randomized controlled trials (RCTs) and observational studies. Primary outcomes were change in motor function and dyskinesia. Secondary outcomes included adverse events and side effects. All studies were analyzed for risk of bias. Results: Fifteen studies, including six RCTs, were analyzed. Of these, 12/15 (80%) mention concomitant treatment with antiparkinsonian medications, most commonly levodopa. Primary outcomes were most often measured using the Unified Parkinson Disease Rating Scale (UPDRS) among RCTs and patient self-report of symptom improvement was widely used among observational studies. Most of the observational data lacking appropriate controls had effect estimates favoring the intervention. However, the controlled studies demonstrated no significant motor symptom improvement overall. The meta-analysis of three RCTs, including a total of 83 patients, did not demonstrate a statistically significant improvement in UPDRS III score variation (MD −0.21, 95% CI −4.15 to 3.72; p  = 0.92) with MC use. Only one study reported statistically significant improvement in dyskinesia ( p  < 0.05). The intervention was generally well tolerated. All RCTs had a high risk of bias. Conclusion: Although observational studies establish subjective symptom alleviation and interest in MC among PD patients, there is insufficient evidence to support its integration into clinical practice for motor symptom treatment. This is primarily due to lack of good quality data.